2007
DOI: 10.1029/2007ja012503
|View full text |Cite
|
Sign up to set email alerts
|

Modification of interplanetary shocks near the bow shock and through the magnetosheath

Abstract: [1] Fast forward interplanetary (IP) shocks have been identified as a source of the largest geomagnetic disturbances. These shocks can evolve in the solar wind, and they are modified both by interaction with the bow shock and during their propagation through the magnetosheath. Our contribution continues the study of the evolution of IP shocks in the magnetosheath. We compare profiles of the magnetic field and plasma parameters observed in the magnetosheath with profiles of the same parameters predicted by an M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
5
34
3
Order By: Relevance
“…This rarefaction wave could result in outward bow shock motion. In MHD simulations, the bow shock begins moving earthward immediately after an encounter with an IP shock at velocities of ∼100 km s −1 (Samsonov et al, 2006). Results from a three-dimensional magnetosheath numerical model show that both a fast reverse shock and a fast expansion wave (rarefaction wave) may result from the interaction of the IP shock with the magnetopause depending on boundary conditions of the model (Samsonov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rarefaction wave could result in outward bow shock motion. In MHD simulations, the bow shock begins moving earthward immediately after an encounter with an IP shock at velocities of ∼100 km s −1 (Samsonov et al, 2006). Results from a three-dimensional magnetosheath numerical model show that both a fast reverse shock and a fast expansion wave (rarefaction wave) may result from the interaction of the IP shock with the magnetopause depending on boundary conditions of the model (Samsonov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of IP shocks with the bow shock has been extensively studied (e.g., Shen and Dryer, 1972;Grib et al, 1979;Zhuang et al, 1981;Samsonov et al, 2006Samsonov et al, , 2007Zhang et al, 2009). In MHD simulations, the interaction of an IP shock with the bow shock launches a fast shock into the magnetosheath and creates a new discontinuity (Zhuang et al, 1981) where the magnetic field strength and density increase, the temperature decreases and the velocity remains unchanged (Samsonov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motion of the indentation can be recorded as two bow shock crossings separated by 1-5 min. Safrankova et al (2007) interpreted out-and inbound bow shock crossing pairs observed by Interball 1 and Geotail as the result of the passage of an interplanetary shock through the magnetosheath. Jelinek et al (2010) found several cases in THEMIS observations when the whole magnetosheath was swept along the probes in a few minutes due to the large displacement of the bow shock and the magnetopause as a result of their interaction with solar wind discontinuities.…”
Section: Discussionmentioning
confidence: 99%
“…The passage of the inbound transmitted shock causes the bow shock and the magnetopause to move inward, while the passage of the sunward-propagating reflected shock causes the boundaries to move out, as confirmed by Pallocchia et al (2010) based on observations aboard Double Star TC1 and Cluster 3. Safrankova et al (2007) suggested that the combination of the inward and outward motions of the bow shock, caused by the transition of an interplanetary shock, results in an indentation of the bow shock surface which flows along the bow shock together with the interplanetary shock. The motion of the indentation can be recorded as two bow shock crossings separated by 1-5 min.…”
Section: Discussionmentioning
confidence: 99%